Integrasi Rantai Pasokan dan Kinerja Operasi : Kapabilitas Rantai Pasokan sebagai Variabel Moderasi - Hani’aturrofidha, Ikrimah; Kusuma, Garry; Putri, Dola Indrayani; Zaitul, Zaitul (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In the era of dynamic competition and increasing supply chain complexity, operational performance is no longer solely determined by internal efficiency, but also by the degree of collaboration across the supply chain. However, previous studies have shown inconsistent findings regarding the direct impact of supply chain integration on operational performance, suggesting the presence of potential moderating variables. This study aims to investigate the effect of supply chain integration on operational performance, with supply chain capability acting as a moderating variable. The study involved a survey of 40 managers and owners of “Toko Serba 35.000” retail stores across the Sumatra region. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0, this research assessed the measurement and structural models through convergent validity, composite reliability, and hypothesis testing. The findings indicate that supply chain integration has a marginally significant positive effect on operational performance. Although supply chain capability alone does not directly influence performance, it significantly moderates the relationship between integration and operational outcomes. This implies that the benefits of integration are maximized when firms possess adequate supply chain capabilities such as agility and responsiveness. The study contributes to the dynamic capability theory by emphasizing the strategic role of internal capabilities in strengthening the impact of inter-organizational integration. Practical implications suggest that retail firms, particularly small and micro enterprises, should invest in developing their supply chain capabilities to leverage integration efforts for improved operational efficiency.